Desenvolvimento e investigação da eficácia de um programa de intervenção para a promoção de funções executivas em alunos do 5º ano do ensino fundamental - Flor, Cristiane Marx (2020)
Executive functions (EF) are a family of interrelated processes that enable the management of new situations and adjustment to changes in a quick and flexible way. Over the years, EF have been better predictors of school achievement, health, wealth and life quality than IQ or social economic status. At school, EF are vital for learning processes, and are regularly required in many different situations of the school day- by-day context. Even though there are many scientific evidences about the importance of EF, executive function processes have not been taught at schools, in an explicit and systematic way. The purpose of this study was to create and assess a program to promote EF called “Stop and Think”, addressed to 5th grade students. Study 1 presents the construction process and search for the program’s validity evidences. The executive processes that are target of intervention in the program are: Metacognition; Emotional Regulation; Organization; Planning/Prioritizing; Working Memory and Cognitive Flexibility. Moreover, the program’s activities were created based on 5th grade Mathematics and Portuguese Language curriculum content and grounded in the Brazilian’s National Basis of Common Curriculum. The program’s first version was submitted to the assessment of judges to verify its clarity, relevance and adequacy of the activities’ levels for 5th graders. After the judges’ assessment, the first version of the program was revised and reedited. The final version has 34 sessions that should be inserted in the regular curriculum of 5th grade Mathematics and Portuguese Language. Study 2 had the purpose to assess the efficacy of the program’s intervention to promote skills related to EF in students from a public school. The participants were 55 5th grade students, divided in an Intervention Group (IG) and a Control Group (CG). All participants were assessed before and after the intervention with the following inventories and scales: Behavior Rating Inventory of Executive Function (BRIEF) - Teachers’ and Parents’ versions, Students’ Self-Perception Inventory towards Studies (SSPIS), My Strengths and Weaknesses towards Studies Questionnaire, and the grades in Mathematics and Portuguese Language provided by the school. The IG’s teacher participated in a 20-hour training with the researcher and mediated 22 sessions of the program, 3 times a week, in school’s regular schedule. Repeated measures of ANOVAs were conducted to compare both groups’ measures before and after intervention. IG presented significative gains in the Global Index of BRIEF- Teachers’ version, as well as in the following subscales: Organization of Materials, Working Memory and Cognitive Flexibility. Positive and significant changes were observed in IG through SSPIS Total Index, as well as in its subscales of Self-regulation and Cognitive Flexibility. Additionally, IG showed superior results when compared to CG in the Portuguese Language grades. However, significant differences in BRIEF-Parents’ version were not seen, neither in Mathematics’ grades. The results show the programs’ positive effects to promote EF components as reported by teachers and students, with academic achievement impact in Portuguese Language.